The Effect of Whistlebowing System toward Fraud Prevention: Mediation of Forensic and Investigative Audit - Imam Abu Hanifah; Vierina Clyde (AFRE (Accounting and Financial Review), 2022)
This study aims to determine the effect of whistleblowing system toward fraud prevention with forensic audit and investigative audit as a mediating variable. The population of this study are auditor in Inspectorate of Banten Province. The result of this study indicates that first, whistleblowing system partially have a positive significant effect on the forensic audit. Second, whistleblowing system partially have a positive significant effect on the investigative audit. Third, whistle-blowing system partially have a positive significant effect on the fraud prevention. Forth, investigative audit partially have a positive significant effect on the fraud pre-vention. Fifth, forensic audit partially have a positive significant effect on the fraud prevention.DOI: https://doi.org/10.26905/afr.v5i2.7530